Programmable biomolecular switches for rewiring flux in Escherichia coli - Gao, Cong (Nat Commun, 2019)
Synthetic biology aims to develop programmable tools to perform complex functions such as redistributing metabolic flux in industrial microorganisms. However, development of protein-level circuits is limited by availability of designable, orthogonal, and composable tools. Here, with the aid of engineered viral proteases and proteolytic signals, we build two sets of controllable protein units, which can be rationally configured to three tools. Using a protease-based dynamic regulation circuit to fine-tune metabolic flow, we achieve 12.63 g L(−1) shikimate titer in minimal medium without inducer. In addition, the carbon catabolite repression is alleviated by protease-based inverter-mediated flux redistribution under multiple carbon sources. By coordinating reaction rate using a protease-based oscillator in E. coli, we achieve d-xylonate productivity of 7.12 g L(−1) h(−1) with a titer of 199.44 g L(−1). These results highlight the applicability of programmable protein switches to metabolic engineering for valuable chemicals production.